The impact of different levels of L-methionine (L-Met) on carcass yield traits, serum metabolites, tibial characters, and profitability of broilers fed conventional diet - Akter, Nasima; Islam, Md Saiful; Zaman, Sharmin; Jahan, Ishrath; Hossain, Mohammad Abul (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: The experiment was undertaken to investigate the performances of broilers with respect to meat yield traits, leg bone quality, blood metabolites, and economic profitability fed conventional diets supplemented with L-methionine (L-Met). Materials and methods: Day-old broiler chicks (n = 144) of either sex were used to conduct the experiment from d1 to 33 days in a battery cage rearing system. Birds were distributed randomly into four dietary treatments, i.e., D0 (DL-Met), D1 (0.20% L-Met), D2 (0.25% L-Met), and D3 (0.30% L-Met) in a completely randomized design. Broiler chicks were fed complete starter ration for the first 2 weeks and then test diets were supplied ad libitum from d15 to 33 days. All the formulated rations had the same calorie and proteinous values. Similar housing, feeding, and rearing management were provided to the birds for all the experimental period. Data on carcass yield traits, such as dressing %, thigh, breast, back, drumstick, shank, neck, and wing weights, etc, were measured on the last day of the trial. Blood serum profile (total protein, glucose, albumin, uric acid, creatinine, and triglycerides), right tibial bone traits (bone weight, bone width), and mineral concentrations (Ca% and P%) were also assessed on the last day of the experiment. The economic profitability of broilers fed on the L-Met diet was also measured in this study. Results: The results revealed that except for dressing % (p < 0.05) and back weight (p < 0.01); all other meat characteristics measured this study were found similar (p > 0.05) between treatments. The highest dressing % and back weight were observed in the D3 group and the lowest being in D0. Blood serum metabolites did not differ (p > 0.05) among treatments. Leg bone traits of broilers were found similar (p > 0.05) between treatments. Higher profit (p < 0.01) and lower production cost (p < 0.05) were observed in the birds fed the D3 diet than other treatments. Conclusion: It can be inferred that broilers might show improved dressed yield and profitable broiler production fed on L-Met supplemented diet (D3). Adv. Vet. Anim. Res., 7(2): 253-259, June 2020